I-LEACH: energy-efficient routing protocol for monitoring of irrigation canals. (August 2015) - Pasha, Muhammad Adeel; Khan, Jahangir Hassan; Masud, Shahid
Irrigation canals and their tributaries, originating from the run of a river, span a considerable geographical area that is typically of the order of 100 km 2 . Efficient deployment of wireless sensor networks (WSNs) to monitor and control the flow of scarce water resources is a challenging task, mainly because the WSN motes are designed to consume very low power and communicate over very short distances. This paper investigates the use of different WSN protocols to monitor water usage over irrigation networks in the province of Punjab, Pakistan. This irrigation network is considered to be among the biggest in the world with over 58, 000 canal outlets. The paper proposes a new energy-efficient routing protocol that improves the network lifespan as well as the packet error rates resulting in a more dependable distributed WSN. The protocol was simulated along with other state-of-the-art protocols in random as well as linear topologies with simulation variables such as the number of nodes, coverage area and base station position varied in each case. The results also show that the node die-out pattern in our protocol is uniformly spread throughout the network as compared with other existing protocols resulting in increased robustness. The NS3 network simulator was used to simulate the geographically distributed WSN with different protocols and system parameters.